2021
DOI: 10.1111/ene.15069
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in Parkinson disease: An updated systematic review and meta‐analysis

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disorder that is known to cause progressive impairment of voluntary motor control [1]. The prevalence of PD has doubled over the past 3 decades, with an estimated 6.1 million individuals living with PD in 2016 [2]. The risk of developing PD increases with age, from 1% of the population older than 60 years to 5% of the population older than 85 years [3,4]. In PD patients, there is loss of dopaminergic neurons in substantia nigra pars compacta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 81 publications
(68 reference statements)
0
16
2
Order By: Relevance
“…“PARKINSONS DISEASE” and “HUNTINGTONS DISEASE” were significantly enriched in cluster B. Patients with neurodegenerative diseases were considered to be at low risk of developing cancer ( Leong et al, 2021 ; Panegyres and Chen, 2021 ). In contrast, the enriched pathways in cluster C were involved in the development and metastasis of cancer ( Zhao et al, 2018 ; Bao et al, 2019 ; Pudełko et al, 2019 ; Wu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…“PARKINSONS DISEASE” and “HUNTINGTONS DISEASE” were significantly enriched in cluster B. Patients with neurodegenerative diseases were considered to be at low risk of developing cancer ( Leong et al, 2021 ; Panegyres and Chen, 2021 ). In contrast, the enriched pathways in cluster C were involved in the development and metastasis of cancer ( Zhao et al, 2018 ; Bao et al, 2019 ; Pudełko et al, 2019 ; Wu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shared environmental risk factors, besides aging [ 3 ], are obesity, diabetes, alcohol abuse, smoking and possibly the gut microbiome [ 4 - 6 ]. Epidemiological data suggest an inverse correlation between PD and cancer [ 7 ], even a significantly lower cancer occurrence in PD patients [ 8 , 9 ]. In addition to the opposing biological mechanisms of both diseases, pharmacological treatment seems to contribute to this interrelationship, too [ 9 ].…”
mentioning
confidence: 99%
“… 3 , 4 , 5 In addition, molecular mechanisms such as mitochondrial dysfunction, excitotoxicity, impaired autophagy, oxidative stress, and genetic mutations are implicated in the degeneration of dopaminergic neurons in PD. 6 Available therapies for PD only affect the symptoms of the disease and mainly focus on the dopaminergic pathway. 2 , 3 , 5 , 7 The most common non-motor symptoms associated with PD involve neurobehavioral complications, sensory problems, and autonomic dysfunction.…”
mentioning
confidence: 99%
“… 2 , 3 , 5 , 7 The most common non-motor symptoms associated with PD involve neurobehavioral complications, sensory problems, and autonomic dysfunction. 6 Several studies have found autonomic dysfunction to be a valuable predictor of cardiovascular morbidity and mortality in PD patients. 8 , 9 Despite the tremendous clinical and epidemiological relevance of these studies, Sudden Death in PD (SUDPAR), a rare but fatal event, contributes to the increased mortality in PD patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation